2000
DOI: 10.1002/1531-8249(200006)47:6<739::aid-ana6>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E facilitates neuritic and cerebrovascular plaque formation in an Alzheimer's disease model

Abstract: The ε4 allele of apolipoprotein E (ApoE) is an important genetic risk factor for Alzheimer's disease (AD). Increasing evidence suggests that this association may be linked to the ability of ApoE to interact with the amyloid‐β (Aβ) peptide and influence its concentration and structure. To determine the effect of ApoE on Aβ and other AD pathology in vivo, we used APPsw transgenic mice and ApoE knockout (−/−) mice to generate APPsw animals that carried two (ApoE +/+), one (ApoE +/−), or no copies (ApoE −/−) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 282 publications
(102 citation statements)
references
References 56 publications
6
96
0
Order By: Relevance
“…We have recently found that Ah [25][26][27][28][29][30][31][32][33][34][35] , an active fragment of the Ah peptide, increased MMP-9 protein levels in cultures of murine cerebral endothelial cells (CECs) in a time -and dose-dependent manner [17]. Increases in MMP-9 were observed at doses as low as 5 AM and within 8 h of treatment.…”
Section: Ab Induces Mmp-9 and Ecm-degrading Activity In Cerebral Endomentioning
confidence: 99%
“…We have recently found that Ah [25][26][27][28][29][30][31][32][33][34][35] , an active fragment of the Ah peptide, increased MMP-9 protein levels in cultures of murine cerebral endothelial cells (CECs) in a time -and dose-dependent manner [17]. Increases in MMP-9 were observed at doses as low as 5 AM and within 8 h of treatment.…”
Section: Ab Induces Mmp-9 and Ecm-degrading Activity In Cerebral Endomentioning
confidence: 99%
“…ApoE that binds to Ab with high affinity Sanan et al 1994;Näslund et al 1995) is enriched in parenchymal or cerebrovascular amyloid deposits and in neurofibrillary tangles in the brains of AD patients and of amyloid-b protein precursor (APP) transgenic mice that serve as a model for AD (Namba et al 1991;Wisniewski and Frangione 1992;Strittmatter et al 1993;Benzing and Mufson 1995). Genetic ablation of apoE leads to a reduction in Ab deposition, despite unchanged Ab generation, in APPtransgenic mice (Bales et al 1997(Bales et al , 1999Holtzman et al 2000). The interactions of apoE with APP/Ab via its receptors modulate Ab processing, clearance and degradation in the brain (Zhao et al 1993;Koistinaho et al 2004;Offe et al 2006;Deane et al 2008;Jiang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The ApoE4 allele, on the other hand, has definitely been linked to increased risk of getting sporadic AD and cerebral amyloid angiopathy (CAA), thus suggesting that it can possibly modify Ab structure, clearance, and neurotoxicity in vivo. Neutralizing the chaperone effect of ApoE4 may have an ameliorating effect on Ab deposition, as has been shown in APP/ApoE À/À double transgenic mice [157,158]. ApoE4 has been shown to bind Ab12-28 and form insoluble micellar structures.…”
Section: Enhancing Ab and Amyloid Clearancementioning
confidence: 85%